IBD prevalence in Lothian, Scotland, derived by capture–recapture methodology. Issue 11 (11th July 2019) - Jones, Gareth-Rhys; Lyons, Mathew; Plevris, Nikolas; Jenkinson, Philip W; Bisset, Cathy; Burgess, Christopher; Din, Shahida; Fulforth, James; Henderson, Paul; Ho, Gwo-Tzer; Kirkwood, Kathryn; Noble, Colin; et al.
Abstract : Objective: IBD prevalence is estimated to be rising, but no detailed, recent UK data are available. The last reported prevalence estimate in the UK was 0.40% in 2003. We aimed to establish the current, and project future, prevalence in Lothian, Scotland. Design: We conducted an all-age multiparameter search strategy using inpatient IBD international classification of disease (ICD-10) coding (K50/51)(1997–2018), IBD pathology coding (1990–2018), primary and secondary care prescribing data (2009–2018) and a paediatric registry, (1997–2018) to identify 'possible' IBD cases up to 31/08/2018. Diagnoses were manually confirmed through electronic health record review as per Lennard-Jones/Porto criteria. Autoregressive integrated moving average (ARIMA) regression was applied to forecast prevalence to 01/08/2028. Results: In total, 24 601 possible IBD cases were identified of which 10 499 were true positives. The point prevalence for IBD in Lothian on 31/08/2018 was 784/100 000 (UC 432/100 000, Crohn's disease 284/100 000 and IBD unclassified (IBDU) 68/100 000). Capture–recapture methods identified an additional 427 'missed' cases (95% CI 383 to 477) resulting in a 'true' prevalence of 832/100 000 (95% CI 827 to 837). Prevalence increased by 4.3% per year between 2008 and 2018 (95% CI +3.7 to +4.9%, p<0.0001). ARIMA modelling projected a point prevalence on 01/08/2028 of 1.02% (95% CI 0.97% to 1.07%) that will affect an estimated 1.53% (95% CI 1.37% to 1.69%) of those >80 years of age. Conclusions: We report a rigorously validated IBD cohort with all-age point prevalence on 31/08/2018 of 1 in 125, one of the highest worldwide.